Reduction of the principal biharmonic problem for a quadrant to nonsingular integral equations - Mel'nichenko, I. P.; Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The principal biharmonic problem for a quadrant with piecewise-continuous boundary conditions is reduced to a system of nonsingular integral equations.